Knowledge and Risk Factors for Osteoporosis among Pre-elderly - Ramdhani, Muhammad; Mulyadi, Dicky; Arisanti, Nita (Althea Medical Journal, 2015)
Background: Osteoporosis is a disease characterized by abnormal loss of bone density resulting inÂ bones that are brittle and liable to fracture. Most cases of fracture in the world are due to osteoporosis. InÂ Indonesia, the prevalence of osteopenia (early osteoporosis) and of osteoporosis are relatively high. OneÂ of the causes of this situation is the low level of public knowledge about how to prevent osteoporosis. ThisÂ study was conducted to identify the knowledge and risk of osteoporosis among pre-elderly at CipacingVillage Jatinangor District in 2014.Methods: This descriptive study was conducted at Cipacing Village Jatinangor District to 160 respondentsÂ who were classified as pre-elderly (aged 45-59 years) and assessed on knowledge and risk factors forosteoporosis through questionnaire-guided interviews after the informed consent was obtained. TheÂ collected data were presented using frequency distribution.Results: A total of 100 respondents (62.5%) had good knowledge about osteoporosis-related information,Â including definitions, causes, risk factors, signs and symptoms, impacts, and prevention. Most respondents,79 respondents (49.4%), are at risk for osteoporosis.Conclusions: Knowledge of osteoporosis among pre-elderly at Cipacing Village Jatinangor District areÂ largely classified into âgood knowledgeâ category. [AMJ.2015;2(4):608â14]Â DOI:Â 10.15850/amj.v2n4.659